Determining the faculty specific academic literacies needs of first year university students: a mixed methods approach - Sebolai, Kabelo (Journal for Language Teaching, 2022)
For three decades to date, South African universities have been concerned about the levels of academic readiness, also known as the articulation gap, among first time entrants to higher education. The general opinion is that we need further reliable and valid indicators of how prepared high school leavers are to cope with the demands of academic education. This has necessitated both pre- and post-admission assessments, following the administration of which foundational academic support programmes are put in place to help students bridge the articulation gap. These support programmes have included those focusing on developing academic literacies, a multifaceted competence comprising the ability to cope with the discourse demands of academic education. The purpose of these support programmes requires that a proper needs analysis be carried out if they are to have a positive impact on students’ effort to boost their ability to bridge the articulation gap. The aim of this article is to demonstrate how this needs analysis was accomplished for academic literacies through a combination of quantitative and qualitative means. It uses a sample of Law students (n=234) and students in the faculty of Economics and Management Sciences (EMS) (n=2944) at Stellenbosch University to accomplish the quantitative part, and a total of two EMS and three Law lecturer interviewees to realize the qualitative dimension.